(untitled) (Vietnam Journal of Community Medicine, 2021)
Hypertension is a disease that seriously affects the health and life expectancy of the community, playing a major etiological role in target organ damage. The selection of antihypertensive drugs to ensure reasonable safety and effectiveness is always a matter of concern of the medical industry. Applying the cross-sectional method on 2,640 patients being examined and treated for hypertension at Nam Dinh general hospital, it was found that 54.67% female patients accounted for the majority. The age of disease in both sexes is over 50 years old with a relatively high frequency of comorbidities. Most of them were prescribed drug combinations in treatment 77,9%. The group of ACE inhibitors + calcium blockers is the most common combination. ACE inhibitors are also the most commonly prescribed drugs in monotherapy. 11,4% of cases had adverse drug interactions, the most dangerous combination is UCMC + Potassium chloride and UCMC + Spironolactone causing hypokalemia. The most common interaction between beta-blockers and calcium blockers increases the antihypertensive effect.